Functioning domestic wheat market: economic aspect - Abramyk, Mykhailo (Skhid, 2015)
The article aims to explore the formation of competition in the domestic wheat market. To achieve this goal the study used the following methods: analilityko-monographic method the study and elaboration of the literature on the formation and development of the wheat; method of system analysis the study of the analysis of production and export of wheat from Ukraine. The article analyzes the main trends in wheat production in Ukraine. Determined market share of major domestic agro producers and exporters of Ukrainian wheat. Analyzed the geographical structure of exports of wheat from Ukraine. The strategy the competitiveness of domestic wheat market and allow domestic producers to receive a stable income despite the risks of subjective and objective. Originality of research results is the grounding principles for the development of the domestic wheat market in the context of the national orientation of export agribusiness. The results in this paper is an important foundation to address issues related to improving the competitiveness of the wheat market in the financial and economic crisis.